2021
DOI: 10.1021/acschemneuro.1c00457
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Triad of Telomere Length, Inflammation, and Gut Dysbiosis in the Manifestation of Depression

Abstract: Telomere length is an indispensable marker for cellular and biological aging, and it also represents an individual's physical and mental health status. Telomere shortening has been observed in chronic inflammatory conditions, which in turn accelerates aging and risk for psychiatric disorders, including depression. Considering the influence of inflammation and telomere shortening on the gut−brain axis, herein we describe a plausible interplay between telomere attrition, inflammation, and gut dysbiosis in the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 142 publications
1
12
0
Order By: Relevance
“…The bidirectional crosstalk between proinflammatory cytokines and CRF is also well supported . CRF plays a key role in activating the HPA axis and hypersecretion of stress hormones, such as corticosterone, which is closely linked to regulating anxiety, depression, and anhedonia. , In our study, TRD and TRD-FMT rats exhibited an increased population of CRF neurons in the PVN and elevated levels of corticosterone in the systemic circulation. When these animals were treated with SCFAs reverted the increased density of CRF neurons and plasma concentration of corticosterone.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The bidirectional crosstalk between proinflammatory cytokines and CRF is also well supported . CRF plays a key role in activating the HPA axis and hypersecretion of stress hormones, such as corticosterone, which is closely linked to regulating anxiety, depression, and anhedonia. , In our study, TRD and TRD-FMT rats exhibited an increased population of CRF neurons in the PVN and elevated levels of corticosterone in the systemic circulation. When these animals were treated with SCFAs reverted the increased density of CRF neurons and plasma concentration of corticosterone.…”
Section: Discussionsupporting
confidence: 59%
“…It has been reported that about one-third of patients with depression may encounter TRD in their lives. , Thus, the discovery of new therapeutics is required to overturn these unmet medical needs. Recent studies highlighted the importance of gut microbiota in the development of mental disorders, including depression. Administration of several gut microbiota-modifying interventions like probiotics, such as Lactobacillus reuteri NK33, Lactobacillus paracasei PS23, Lactobacillus plantarum MTCC 9510 , Lactobacillus kefiranofaciens ZW3, Lactobacillus gasseri CP2305, Bifidobacterium breve UBBr-01, and Bifidobacterium infantis UBBI-01, and prebiotics, such as polyphenols, polysaccharides, and dietary fibers, exerted robust antidepressant-like phenotypes in animals by promoting the colonization of other beneficial microorganisms in the host. However, clinical outcomes of probiotics/prebiotics in human studies are still debatable and inconclusive. , …”
Section: Introductionmentioning
confidence: 99%
“…Table 8 [158][159][160][161][162][163] illustrates examples of the relationship between inflammation, oxidative damage and telomere length. It should be noted that efforts to minimize the symptoms of NCDs rather than correcting underlying systems biology defects (e.g., unresolving tissue inflammation) have two very negative outcomes.…”
Section: Inflammation Oxidative Stress and The Longevity Cyclementioning
confidence: 99%
“…Linking telomere length, inflammation, and gut dysbiosis. [158] Oxidative stress damages telomeres and mitochondria. [159] Early life factors program both inflammation and telomere shortening.…”
Section: Inflammatory Damage and Telomere Status Reference(s)mentioning
confidence: 99%
“…Symptom-only management should be viewed at best as a transient goal when compared to disease-free, life-extending therapeutic outcomes. Linking telomere length, inflammation and gut dysbiosis [158] Oxidative stress damages telomeres and mitochondria [159] Early life factors program both inflammation and telomere shortening [160] Chronic inflammation generates immune aging and cross talk with the telomere complex [161] Link between telomere shortening and tissue inflammation [162] Proposal that inflammation, telomere length, and microbiota may form a loop.…”
Section: Inflammation Oxidative Stress and The Longevity Cyclementioning
confidence: 99%